Study of Intermolecular Interactions between 2-Chloroaniline Isomeric Butanol Complexes in Gas Phase by Using DFT, NBO, QTAIM and RDG Analysis - Sekhar, M.Chandra; Wakgari, Dereje; Kenie, Dunkana Negussa; Reddy, K. Chandrasekhar (Asian Journal of Chemistry, 2019)
Density functional theoretical (DFT) studies on intermolecular hydrogen bond interactions between self and cross-associated molecular complexes of 2-chloroaniline and isomeric butanols (e.g., 2-methyl-2-propanol, 2-methyl-1-propanol, 2-butanol and1-butanol) have been analyzed in gas phase. Thirteen 2-chloroaniline isomeric butanol complexes are analyzed at B3LYP/6-311++G(d,p) level regarding their geometries, bond characteristics and interaction energies. The second-order perturbation stabilization energy has been calculated by natural bond orbitals analysis. Barder's quantum theory of atoms in molecules are employed to elucidate electron density (ρ) as well as its Laplacian (∇2ρ) of the complexes. Further to evaluate the strong and weak interactions between the selected molecular complexes non-covalent interactions plots we used the reduced gradient method.